Humidade Ascensional em Paredes de Construções Históricas - Maria Isabel Morais Torres (2004)
The problems of building heritage brought up, nowadays, an unprecedented interest that affects political decisions and cultural tendencies. To intervene in the building heritage, the demand of a more and more rigorous and objective knowledge of the reality is needed to act and operate.Rising damp is one of the main causes of degradation of historical constructions, being the most registered and observed pathology and also one of the most complex problems to treat and resolve.In the present work the fundamental mechanisms of heat and moisture transport are analysed and described with several mathematical models and computational programs that from theyresult.A data-base was created with the physical and hygro-thermal properties of various construction materials, indispensable for the use in numerical simulations of these phenomena's in study. Wall specimens were constructed with the main goal to characterizeexperimentally the rising damp phenomena in walls of historical constructions, and also, in particular the efficiency of a proposed treatment system was analysed: ventilation of the base of the walls.The use of a two-dimensional numerical approach, allowed the simulation of the heat and moisture transfer, to further evaluate the behaviour of the wall faces to the rising damp progression, for different border conditions.It is also presented a case of application of the proposed system of treatment (ventilation of the base of the walls) to a XI century Church located in the north of Portugal.KEY-WORDS: Damp, rising damp, wall, historical construction, hygro-thermal properties, rising damp measurements, numerical simulation